Penyusunan Bahan Ajar Online dalam Kontribusi Merdeka Belajar bagi Guru MTs di Tangerang - Arjulayana, Arjulayana; Gunawan, Yudhie Indra; Tri Pujiati (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
Arranging online teaching materials is a necessity in the current digital era, especially for educators/teachers. Teaching materials are one of the learning tools that can become a reference for a teacher as an effort to provide information and knowledge in a structured teaching strategy. This paper aims to provide an explanation regarding the implementation of community service carried out by MTS teachers in Tangerang in the context of preparing online teaching materials through an online application. There are 45 participants who involved in this program to arrange online teaching materials, from those participants only 1 person is succeed and the others found it difficult to complete it, because they were also busy. This shows that the implementation of teaching materials for a teacher is still low.